UJI POTENSI EKSTRAK DAUN BENALU BATU (BEGONIA SP) TERHADAP KADAR GLUKOSA DALAM DARAH DAN GAMBARAN HISTOPATOLOGI PANKREAS TIKUS PUTIH JANTAN (RATTUS NORVEGICUS) - Joni Tandi; Dela Erni Paerunan; Nurifa Nurifa; Yunlis Silintowe Kenta; Sri Mulyani (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
This study aims to determine the potential for glucose levels in the blood of ethanol extracts of the begonias (Begonia Sp.), the effect of the extract on the pancreatic histopathology of white rats (Rattus norvegicus) which was induced by streptozotocin, and the effective dose begonias’ extract leaves on the histopathological descriptions of pancreatic male white rats. This study was an experimental laboratory where the research group consisted of group I (the control group) as a normal control was given a standard feed, group II (negative control) was given a 0.5% Na CMC suspension, group III (positive control) was orally given glibenclamide and experimental groups IV, V, and VI (doses 50, 100, and 200 mg/kg BW). Were given ethanol extract of begonias leaves. The results showed that the ethanol extract of the begonias (Begonia Sp.) contained secondary metabolite compounds, namely flavonoids, alkaloids, saponins, polyphenols, and tannins. Ethanol extract of begonias leaves at adose of 50 mg/kg BW was an affective dose in reducing blood glucoselevels by an avarage of 101,8 mg/dL) and a dose of 50 mg/kg BW can affect the histopathological picture of the pancreas in STZ induuced rats with an average damage value of 2 from a maximum of 4.